A Combination of eye exercises and warm compresses against eye fatigue in computer user employees - Octavariny, Raisha; Widyaningsih, Fadlillah; Rambey, Harris; Farhana, Jahirah (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Using computers for long periods of time can cause various health problems, especially the eyes. According to the American Optometric Association (AOA), the symptoms mentioned, such as eye strain and difficulty focusing, are common in people who frequently use computers for more than 2 hours at work. Therefore, it is important for workers who use computers as a primary aid to take steps to protect their eye health. This type of research is a type of quantitative research, namely quasi-experimental pre-test post-test one group design. This design uses only one group, namely the Experiment group without the Control group. Pre-test and post-test techniques will be carried out on employees using computers at BPJS Claims. The flow of this research is that the researcher conducts a pretest on the sample then is given treatment, after being given treatment then a post test is carried out. Based on the results of the Nonparametric Test using the Wilcoxon Test, the p value (0.001) ? (0.05) can be concluded that the hypothesis in the study is accepted, meaning that there are differences in the level of eye fatigue before and after Eye Exercises and Warm Compresses for Computer User Employees at Grandmed Lubuk Pakam Hospital . Based on the measurement results using the observation sheet, most of the employees experienced moderate eye fatigue as many as 12 people, therefore it is expected that computer users can apply the interventions provided and become input and increase workers' knowledge about occupational diseases that arise due to work and are also expected to reduce the level of eye fatigue that occurs in workers.